Relationship between peripheral and mesenteric serum levels of CEA and CA 242 with staging and histopathological variables in colorectal adenocarcinoma - Cardoso,Mauro Lamelas (2009)
PURPOSE: To compare histopathological variables and staging in colorectal adenocarcinoma cases with CEA and CA 242 in peripheral and mesenteric blood. METHODS: In 169 individuals underwent surgery for colorectal cancer, CEA and CA 242 were analyzed and compared to mesenteric and peripheral blood and correlated with macroscopic tumor's morphology and size, degree of cell differentiation, venous, neural and lymphatic involvement and TNM classification. RESULTS: There was a difference between the mesenteric (M) and peripheral (P) serum levels of CEA (p=0.020). Higher levels of markers were correlated with venous invasion CEA (P) p=0.013, CEA (M) p=0.05, CA 242 (M) p=0.005 and CA 242 (P) p=0.038; with advanced staging CEA (P) < CEA (M) (p < 0.05); CA 242 (P) < CA 242 (M) (p < 0.05); and with greater dimensions CEA (P) < CEA (M) (p < 0.001); CA 242 (P) < CA 242 (M) (p < 0.001). CA 242 became higher with neural invasion (P): p=0.014, (M): p=0.003). CONCLUSIONS: There were higher mesenteric than peripheral levels of CEA. Both mesenteric and peripheral levels of CEA and CA 242 were higher in neoplasm with venous involvement, greater diameter and advanced stages. There was a correlation between CA 242 and neural invasion.